Metal-organic framework derived ultralow-loading platinum-copper catalyst: a highly active and durable bifunctional electrocatalyst for oxygen-reduction and evolution reactions. (17th May 2021) - Parkash, Anand
Abstract: Electrocatalysts with high active oxygen reduction (ORR) and oxygen evolution reaction (OER) activities are key factors in renewable energy technologies. Unlike common strategies for adjusting the proportion of metal centers in a multi-metal organic framework (MOF), herein, we designed and synthesized bifunctional electrocatalysts using cetyltrimethylammonium bromide (CTAB)-capped ultra-low content platinum (Pt) (≤0.5 wt.% Pt) and copper (Cu) nanoparticles and doped on the surface of zinc-based MOF (Zn-MOF-74) and calcinated at 900 °C. According to the electrochemical activity, the Pt/Cu/NPC-900 exhibits superior catalytic activities towards both the ORR with the onset ( E 0 ) and half-wave ( E 1/2 ) potentials were 1.0 V and 0.89 V versus RHE, respectively, and OER ( E o = 1.48 V versus RHE and overpotential ( η ) = 0.265 V versus RHE) in an alkaline electrolyte at ambient temperature. Also, Pt/Cu/NPC-900 catalyzes through a 4 - electron process and exhibits superior stability. Such insightful findings, as well as a newly developed approach, provides rational design and synthesis of an economical and efficient strategy for bifunctional electrocatalyst development.